2014
DOI: 10.1590/1809-4503201400030006
|View full text |Cite
|
Sign up to set email alerts
|

Female homicide in Rio Grande do Sul, Brazil

Abstract: ABSTRACT:This study aimed to assess the female homicide rate due to aggression in Rio Grande do Sul, Brazil, using this as a "proxy" of femicide. This was an ecological study which correlated the female homicide rate due to aggression in Rio Grande do Sul, according to the 35 microregions defined by the Brazilian Institute of Geography and Statistics (IBGE), with socioeconomic and demographic variables access and health indicators. Pearson's correlation test was performed with the selected variables. After thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 13 publications
(9 reference statements)
2
21
0
1
Order By: Relevance
“…The positive association between demographic density and homicide has been previously demonstrated in this country 25 26 ; however, other studies did not report this association. 27–29 In our study, mesoregions with high HDI values, such as the Metropolitan, North Central and West, were involved in the HH clusters.…”
Section: Discussionmentioning
confidence: 75%
“…The positive association between demographic density and homicide has been previously demonstrated in this country 25 26 ; however, other studies did not report this association. 27–29 In our study, mesoregions with high HDI values, such as the Metropolitan, North Central and West, were involved in the HH clusters.…”
Section: Discussionmentioning
confidence: 75%
“…Work in the global south has invoked structural violence to understand historical trauma, 12 poverty, and gender inequality. [13][14][15] Much of this work is qualitative, often based on semi-structured interviews. Structural violence, in this tradition, is a framework to help contextualize and make sense of a study's findings.…”
Section: Use Of "Structural Violence" In Health Studiesmentioning
confidence: 99%
“…It is believed that, in the state of RS and in rural regions of agropastoral economic matrix, there is a marked appreciation of male sexual roles, in which sexist behavior is evidenced. This contributes in some way to the increase in female deaths, 19 of which is an aspect evidenced by the research data, in which homicides showed a significant increase in their occurrences over the years analyzed.…”
Section: Discussionmentioning
confidence: 73%